Coaching Innovation Islamic Education of Muallaf - Raihan, Raihan; Muslih, Imam; Firdaus, Firdaus; Khasanah, Uswatun (AMCA, 2025)
In Indonesia, the number of converts has increased. Data from Muallaf Center Indonesia recorded that since 2003 the number of converts is more than 50,000 people. The process of converting a person to Islam is carried out in various mosques, including those that are the object of research, namely; Istiqlal Mosque (Mosque I) Al Musyawarah Grand Mosque (Mosque II), Pondok Indah Grand Mosque (Mosque III), At Tiin Grand Mosque (Mosque IV), Al Azhar Grand Mosque (Mosque V) Sunda Kelapa Grand Mosque (Mosque VI), Lautse Mosque Jakarta (Mosque VII), and Lautze Mosque Bandung (Mosque VIII). The purpose of this research: 1). Identifying and analyzing the motivation of converts. 2). Analyzing the general tendency of converts' behavior. 3). Innovating the Islamic Education Development of Muslim converts. The research methodology was conducted using the phenomenological method. The research results obtained: (1). The muallaf's understanding of his decision to become a muallaf is in four categories: 1) normative, 2) pragmatic, 3) situational while the general tendency of muallaf behavior is in three categories: 1). Dzalim li nafsih, (harming oneself / neglecting worship). 2). Muqtashid, (moderate/performing the obligations of basic religious teachings).